Comparison Outcomes of Opening-Wedge High Tibial Osteotomy without Bone Graft and Unicondylar Knee Replacement at 5-year Follow up - Sungkhun, Pawaris (Journal of Southeast Asian Orthopaedics, 2021)
Purpose: The purpose of this study is to compare midterm outcomes of opening-wedge high tibial osteotomy (HTO) without bone graft and unicompartmental arthroplasty (UKA) in advance medial compartment arthritis. Materials and Methods: Fifty patients were divided into the HTO (n=20) and UKA (n=30) groups. Clinically, we evaluated range of motion, the Oxford knee scoring scale, and Knee Society Score at the five years follow-up postoperatively. Results: All clinical outcomes gradually improved in both groups from the postoperative period to the final follow-up. At the final follow-up, all clinical outcomes were slightly better in the HTO group than in the UKA group; however, differences were not statistically significant. Conclusions: HTO is comparable to UKA in terms of clinical outcomes. Thus, the results of this study suggest that HTO might be a good alternative treatment to UKA for medial unicompartmental arthritis.